Menumbuhkan Semangat Belajar di Sekolah Pelosok Desa Tete Batu - Aliza, Mardian; Sayutiani, Farah; Amanda, Riski (Journal of Community Development and Empowerment, 2025)
This community service program was carried out with the aim of fostering students’ motivation to learn in remote schools in Tete Batu Village, where they face limitations in educational facilities, access to information, and low learning motivation due to socioeconomic conditions. The activities focus on an empowerment-based approach through learning assistance, training in creative learning methods, and strengthening the capacity of teachers and the school environment. The methods used include initial observations to map needs, interactive workshops, the provision of teaching materials based on educational games, and motivational sessions involving teachers, parents, and community leaders. The results of the program show an increase in students’ enthusiasm for learning, as reflected in improved activeness, participation, and perseverance in completing tasks. Teachers also reported enhanced skills in applying creative learning methods that better suit the characteristics of students in remote areas. Additionally, parental support for their children's learning increased after they were involved in community discussions. This program emphasizes that collaboration between educators, the community, and education volunteers plays an important role in fostering learning motivation in remote areas. Program sustainability can be achieved through periodic mentoring and the provision of simple learning media that are easy to replicate. Thus, this initiative makes a tangible contribution to efforts to equalize education quality and strengthen students’ motivation to learn in Tete Batu Village.